Remoção de matéria orgânica e cor de efluente kraft por adsorção usando carvão ativado e argila - Hinojosa, Eduardo Alberto Lazo (2014)
Nowadays, there is a concern of society regarding the impacts caused by the industries on the environment. Large amounts of water, wood and chemichal are used to produce cellulose and paper, and contaminated effluents are generated through the various industrial processes associated. The organic matter and the color of the Kraft effluent are due to the presence of lignin-derived molecules that are difficult to be removed or biodegraded. With intent to remediate this effluent, this study aim to evaluate the removal of color and residual organic matter from biologically pretreated Kraft effluent, using activated carbon from coconut shell and montmorillonite clay by adsorption method through experimental designs. For the color and organic matter removal, the following factors were evaluated: a) pH of the effluent; b) the mass of the adsorbent material in the adsorption process and c) temperature. The adsorption capacity of organic matter and color in the activated carbon and in the montmorillonite clay were determined by the mathematical model of Langmuir and Freundlich, by means of isotherm adsorption construction in Kraft effluent.The effluent was characterized by COD, DBO5,20, COT and true color before and after the tertiary treatment. For it treatment two temperatures were employed: 25 °C and 40 °C, followed by a 32 full factorial design with center point in triplicate, using pH (5.0, 6.0 and 7.0) and masses of adsorbent material (0.5, 1.0 and 1.5 g) as variables. The experimental design used showed that the best results with activated carbon are obtained at 40 ° C, pH 7.0 and 1.5 g of adsorbent with removals of 98% of TOC, 83% of COD, 97% of BOD5,25 and 95% of true color. With clay, the best results occurred at temperature of 40 ° C, pH 7, and 1.5 g of adsorbent to remove 55% of COT, 50% of COD, 90% of BOD5,20 and 56% of true color. The main responsible for the removal of color and organic matter was the mass of adsorbent, followed by the pH. It was also evaluated the possibility of using the residue obtained from the adsorption process in the incorporation of carbon ash to produce mortars with levels of 0.4%, 1.0% and 1.2% in Portland cement, sand and water, with curing times of 7 and 28 days, for which compressive strength tests were performed. To reuse the clay, 15% of the clay from the adsorption process was used, together with 25% of glass and 60% of red clay, in order to construct ceramics bodies specimen generated at temperatures from 1100 °C to 1150 °C. The treatment process proposed in this work using activated carbon demonstrated to be, in general, a good alternative compared to montmorillonite clay for the color reduction and residual organic matter removal from Kraft process effluent, while residues from both process can be used as aggregates for mortars and ceramic body production.